2013
DOI: 10.1007/s13659-013-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive natural products from marine angiosperms: abundance and functions

Abstract: This review explores the natural products of seagrass that are to be exploited for their bioactive potential. Beside from portraying the presence of a wide array of secondary compounds such as phenols, flavonoids, sterols and lipids from different seagrass species, the focus is on novel natural products projecting towards their biological applications. Though there are a significant number of reports on the abundance of secondary metabolites from seagrass and their bioactive derivatives, only a small number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 74 publications
1
46
0
12
Order By: Relevance
“…There are more than 70 species of seagrasses worldwide [2], but only four species of seagrasses have been found in European waters, namely Zostera marina L. (eelgrass), Zostera noltii (dwarf eelgrass), Cymodoceanodosa and Posidoniaoceanica [1]. Two of these: Z. marina and Z. noltii, are native to Norwegian coastal waters, in addition to Z. angustifolia which is considered as a variety of Z. marina.…”
Section: Introductionmentioning
confidence: 99%
“…There are more than 70 species of seagrasses worldwide [2], but only four species of seagrasses have been found in European waters, namely Zostera marina L. (eelgrass), Zostera noltii (dwarf eelgrass), Cymodoceanodosa and Posidoniaoceanica [1]. Two of these: Z. marina and Z. noltii, are native to Norwegian coastal waters, in addition to Z. angustifolia which is considered as a variety of Z. marina.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids (diosmetin 7‐sulfate) and phenolic acids (coutaric and caftaric acid), detected in C. nodosa , are known as phenolic compounds, defensive secondary plant metabolites. They have antiherbivory properties, antimicrobial activity, helping in the nutrient storage by protecting oxidation of fatty acids, and also protecting marine macrophytes and seaweeds against pathogen attacks and harmful ultraviolet radiation . In process of adaptation to environmental conditions, such as marine water salinity, temperature, UV light exposure, presence of other marine organisms, seagrass and seaweeds produce different biologically active compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In early studies, myricetin, quercetin, kaempferol, apigenin, luteolin, and gallic acid were reported in angiosperms including the Hamamelidae, Rutaceae, Eriocaulaceae, Lythraceae, and Velloziaceae (Grieve and Scora, 1980;Giannasi, 1986;Salatino et al, 2000). Several phenolic compounds, such as p-coumaric acid, caffeic acid, ferulic acid, protocatechuic acid, gallic acid, vanillic acid, and flavonoids like luteolin, apigenin, have also been identified in seagrasses (Subhashini et al, 2013). Apigenin, kaempferol, luteolin, myricetin, quercetin, and rutin were identified in some Iranian flowering plants from different families including the Leguminosae, Polygonaceae, Euphorbiaceae, Resedaceae, and Cyperaceae (Mitra, 2012).…”
Section: Phytochemicals Of Ferns and Their Distribution In Other Planmentioning
confidence: 99%